Risk Attitudes and Informal Employment in Ukraine - Thomas Dohmen; Melanie Khamis; Hartmut Lehmann; Norberto Pignatti (Institute of Labor Economics (IZA), 2023)
Using data from the four waves of the Ukrainian Longitudinal Monitoring Survey - ULMS (2003, 2004, 2007 and 2012), we analyze whether workers with a higher willingness to take risks are more likely to select into informal employment contracts. The data permit us to distinguish between five employment states: formal and informal self-employment, formal salaried employment, voluntary informal salaried employment, and involuntary informal salaried employment. The empirical evidence reveals risk attitudes as a strong causal determinant of the incidence of all types of informal employment but involuntary informal salaried employment. We also provide evidence that our results are not driven by reverse causality: risk attitudes impact on the choice of employment state whilst this latter does not influence risk attitudes. Linking risk attitudes with selection into employment states, we also can establish that along the formal-informal divide the Ukrainian labor market is predominantly segmented for salaried workers whilst it is integrated for the self-employed.
Keywords: D91; J42; J46; P23; 330; risk attitudes; informal employment; labor market segmentation; Ukraine